Characterization of cyclin dependent kinase-7 and its differential response to grafting challenge in the black shell colored selected line of pearl oyster Pinctada fucata martensii. Issue 101 (June 2020) - Adzigbli, Linda; Zhao, Zihan; Wang, Ziman; Yang, Chuangye; Hao, Ruijuan; Deng, Yuewen
Abstract: Cyclin dependent kinase-7 (Cdk-7) is a protein kinase associated with regulating the cell cycle, cell differentiation and proliferation, apoptosis and inflammatory response. This study characterized the full cDNA sequence of Cdk-7 in Pinctada fucata martensii (PmCdk-7). A full length sequence of 1473bp with an open reading frame (ORF) of 915bp and encodes a 304aa, 5′-UTR of 58bp and a 3′-UTR of 500bp was obtained. The construed amino acid sequence of PmCdk-7 comprised of a Serine/Threonine protein kinases, catalytic (S_TKc) domain with a p rotein kinases ATP-binding region signature (14-38aa) and the serine/Threonine protein kinases active-site signature (129-141aa) within the domain. Tissue distribution analysis revealed a high relative mRNA expression of PmCdk-7 within haemocytes. Following the insertion operation (grafting), the relative expression levels of PmCdk-7 in the haemocyte was expressed differentially among the studied groups; the black shell colored selected line (BS) and the control group (CG). High expression was recorded between 12 h and 5d with a peak at 3d suggesting a heightened level of DNA replication and inflammatory response during the pearl-sac formation and this expression was higher in BS than CS showcasing, the heightened immune capacity of BS to grafting operation. Immune stimulation experiment with bacterial endotoxin and a viral mimic revealed PmCdk-7 response to pathogenic stress. The results from our study showed that PmCdk-7 performs a vital function during the cell cycle by aiding DNA replication and also aid response to inflammations generated due to the incision from the grafting operation and long exposure to immune-stimulants (pathogens). Highlights: We characterized the Cdk-7 gene and its differential response in the pearl oyster P. fucata martensii . PmCdk-7 contains a Serine/Threonine protein kinases, catalytic (S_TKc) domain. PmCdk-7 was highly expressed in haemocytes and gills. The black shell colored line of P. fucata martensii recorded a higher PmCdk-7 expression to grafting. PmCdk-7 exhibits an immune response function during the pearl-sac formation and to pathogenic attacks.